ИНДУСТРИЯ 4.0 ЖАҒДАЙЫНДА ЖЕТКІЗУ ТІЗБЕГІН БАСҚАРУ: ЖҮЙЕЛІ ӘДЕБИЕТ ТАЛДАУЫ (Экономика: стратегия и практика)
The fourth industrial revolution creates new conditions for supply chain management in logistics. The purpose of this article is to determine the main directions of research based on the analysis of the scientific literature on supply chain management in Industry 4.0. To achieve this goal, a systematic bibliographic analysis was used: a search was carried out by keyword on the Web of Science (WoS) and Scopus databases. Materials were reviewed by year, industry, authors, countries. Further, the materials were limited to the disciplines and analyzed the most cited articles. In research on supply chain management under the conditions of Industry 4.0, the following research topics were identified: new trends in supply chain management; operational management of Smart manufacturing; Lean manufacturing, environmentally sustainable production, production management issues in new conditions; New technologies in supply chain management (Internet of things (IoT), big data, cloud computing, cyber-physical systems, automation systems, RFID technologies, mobile applications, etc.). It is possible to effectively organize the supply chain using these technological opportunities. The introduction of the supply chain management system into the processing industry has many advantages. The active use of Industry 4.0 technology in ensuring the production of raw materials, organizing the production cycle, distributing products through retail chains, delivering finished products to the final consumer influences the reduction of production costs, as a result of which the competitiveness of the enterprise will increase.